Faktor Penentu Permeasi Transdermal:Tinjauan Berdasarkan Hukum Fick I - Binarjo, Annas (UI Scholars Hub, 2012)
Transdermal drug delivery may be an alternative to overcome the problems of oral administration, such as fluctuations drugconcentration in the blood. Only several drugs have a good transdermal permeation ability, thus some efforts are needed to improve it. Transdermal permeation follows pasive diffusion mechanism. Therefore, Fick Law I must be concidered in improving transdermal permeation of the drug. This review aims to determine the factors associated with the transdermal permeation based on Fick's law I. Chemical compounds to enhance transdermal permeation (Chemical penetration enhancers) can be used to increase the diffusion coefficient (D), the partition coefficient (k), the rate of drug in the donor compartment (Cd), membrane thickness (h), and extensive contact of drug with the skin (S).